Effect of D3 dopamine receptor on dopamine D4 receptor expression and function in renal proximal tubule cells from Wistar–Kyoto rats and spontaneously hypertensive rats. Issue 8 (August 2016) - Chen, Xinjian; Liu, Yukai; Wang, Wei E.; Chen, Caiyu; Ren, Hongmei; Zheng, Shuo; Zhou, Lin; Zeng, Chunyu
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Dopamine receptors induce natriuresis in kidney. Previous studies have shown interactions between different subtypes of dopamine receptors in renal proximal tubule (RPT) cells. We hypothesize that D3 receptors have an interaction with D4 receptors in RPT cells from normotensive rats (Wistar-Kyoto, WKY) and spontaneously hypertensive rats (SHRs). Methods: Immunoblotting and reverse transcriptase-polymerase chain reaction (RT-PCR) were used to examine the expression of D3 and D4 receptors. Na + –K + -ATPase activity was used to measure the function of receptors. The distribution and colocalization of D3 and D4 receptors were detected by confocal microscopy and co-immunoprecipitation. Results: D3 receptor agonist PD128907 increased the mRNA and protein expression of D4 receptors in RPT cells from WKY rats, but decreased that from SHRs. In the presence of PLC blocker (U73122, 10− 6 mol/l) or PKC inhibitor 19 -31 (10− 6 mol/l), the up-regulation of D3 receptor on D4 receptor was lost in WKY cells. Moreover, stimulation with PD128907 for 30 minutes decreased D4 receptor degradation in WKY cells, not in SHR cells. D3 and D4 receptors colocalized and co-immunoprecipitated in RPT cells. PD128907 increased co-immunoprecipitation of D3 and D4 receptors in WKY RPT cells, but not in SHR RPT cells. Pre-treatment with D3 receptor agonist also increases D4 receptor mediated inhibitory effect on Na + –K + -ATPase activity in WKY cells, but not in SHR cells. Conclusion: Renal D3 receptor regulates the expression and function of D4 receptor in RPT cells via PLC /PKC signaling pathway, the loss of this interaction might be involved in the pathogenesis of hypertension.